2020
DOI: 10.1111/een.12874
|View full text |Cite
|
Sign up to set email alerts
|

Feeding patterns revealed host partitioning in a community of frog‐biting mosquitoes

Abstract: 1. Resource partitioning is a critical component in competing species that coexist in a community. The biting behaviour of coexisting frog‐biting mosquito species associated with a tropical anuran community is investigated. 2. Monthly samplings were taken for 2 years at two study sites in central Sri Lanka to collect frog‐biting mosquitoes, anuran abundance, environmental data, and interactions between mosquitoes and anuran hosts. Mosquitoes were collected using mouth‐operated aspirators and sound traps broadc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(55 reference statements)
0
5
0
1
Order By: Relevance
“…2019; but see de Silva et al . 2020). In some systems, frog‐biting midges are attracted to a broad range of pure tones, 100–4000 Hz, and are preferentially attracted to tones around 2 kHz (Meuche et al .…”
Section: Introductionmentioning
confidence: 99%
“…2019; but see de Silva et al . 2020). In some systems, frog‐biting midges are attracted to a broad range of pure tones, 100–4000 Hz, and are preferentially attracted to tones around 2 kHz (Meuche et al .…”
Section: Introductionmentioning
confidence: 99%
“…De Silva et al . (2020) in turn found Ma. uniformis feeding regularly on several species of frogs in Sri Lanka and even postulated an attraction to vocalisations.…”
Section: Other Culicid Genera Using Herpetofauna As Blood Sourcesmentioning
confidence: 90%
“…yaeyamana are all also attracted to frog calls (Borkent and Belton 2006; de Silva et al . 2020; Toma et al . 2005, 2014).…”
Section: Searching For Possible Specialist Mosquito Species From the mentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the most abundant groups of insects widespread throughout the country, and many act as vectors of life-threatening diseases such as dengue, chikungunya malaria, lymphatic filariasis and Japanese encephalitis (JE) (Herath et al, 1988;Peiris et al, 1993;Amerasinghe et al, 2002). Recent studies have reported the presence of ornithophilic and frog-biting mosquitoes, potentially vectors of emerging infectious diseases in humans and wildlife (Chathuranga et al, 2018;Chathuranga et al, 2021;de Silva et al, 2020). Accurate and precise identification of these mosquito species and siblings of species complexes is crucial for managing and controlling mosquito-borne diseases.…”
Section: Introductionmentioning
confidence: 99%